Mancing sebagai aktivitas sosial: membentuk solidaritas dan ekonomi komunitas - Pangestu, Guntur Adi (Maliki Interdisciplinary Journal, 2025)
Fishing is not merely an individual recreational activity; it also has significant social and economic dimensions. The interactions among anglers often foster bonds of solidarity, friendship networks, and collective cooperation within the community. Furthermore, this activity stimulates economic activity through the provision of fishing equipment, transportation services, boat rentals, and the emergence of tourism events and fishing competitions. These impacts provide opportunities to strengthen the local economy while creating space for community participation in productive activities. Therefore, fishing can be viewed as a social activity that contributes to the building of solidarity and the sustainable development of the community economy. The discussion on fishing as a social and economic activity shows that this activity is not just a hobby or recreational activity, but also has strategic value for society.